De sociale betekenis van de buurt Een onderzoek naar de relatie tussen het wonen in een arme wijk en sociale mobiliteit - Pinkster, Fenne M. (NICIS, 2008)
In The Social Significance of the Neighbourhood the negative image of the social quality of poor urban districts is critically examined based on research in two districts of The Hague. This investigation focuses on the extent to which living in a certain quarter could constitute as an obstacle to social mobility and what role social relations play between local residents therein. Based on interviews with residents in a poor and a mixed neighborhood this study outlines the role that the neighborhood and local residents play in the social and working lives of residents.